Loan Syndication and Credit Cycles - Ivashina, Victoria; Scharfstein, David (American Economic Review, 2010)
Cyclicality in the supply of business credit has been the focus of a considerable amount of research. This cyclicality can stem from shocks to borrowers’ collateral, which affect firms’ ability to raise capital if agency and information problems are significant (Ben S. Bernanke and Mark Gertler, 1989). Or it can stem from shocks to bank capital, which affects the supply of bank loans if agency and information problems limit the ability of banks to raise additional capital (Bernanke, 1983). In this paper, we examine cyclicality in the supply of credit in the context of modern forms of banking, often referred to as the “originate-to-distribute” model. In particular, we focus on the role of syndicated lending.